New Directions in the Study of African American Recolonization - Miller, Randall M.; Harrold, Stanley; Hetrick, Matthew J.; Tomek, Beverly C. (Book collections on Project MUSE., 2017)
Beginning in 1816, the American Colonization Society worked to send American blacks to resettle in Africa. From inception, however, its foundational ethos has been debated. These debates continued long after the effective end of the ACS during WWI through the Civil Rights movement to today, when even historians among the Press's own authors respectfully hold opposing views. In this volume, Beverly Tomek and Matthew Hetrick gather essays from scholars with different opinions and divergent methodologies, offering not only new research to address some of the old questions about American colonization and missionary activities but also new questions to spur further debate.